Correlation between Insulin Like Growth Factor -1 and Anthropometric Measurements of Premature Infants - Abdelwahab, Amina; Khashana, Abdelmoneim; Ahmed, Nesma; Younis, Soha (Journal of Nepal Paediatric Society, 2016)
Introduction: It is agreed that insulin like growth factor 1 (IGF- 1) influence growth. IGF-1) is a significant endocrine mediator of growth and encourages cellular propagation, survival, and differentiation. The aim of this study was to correlate insulin like growth factor 1 and anthropometric measurements in the neonatal age of the premature infants. Material and Methods: This study was performed at a level III intensive care unit at Suez Canal university hospital, Ismailia, Egypt. It is a cross sectional analytical study in the period from the March 2014 to September 2014. All cases are premature and were imperiled to history taking, clinical examination includes weight, length, head circumference and measurement of serum (IGF-1). Results: There were a total of 40 neonates. Gestational age extended from 31 to 36 weeks with a mean of 34.32±1.68 weeks; weight ranged from 1.15 to 3.20 kg with a mean of 2.14±0.59 kg and length ranged from 37 to 49 cm with a mean of 43.85±3.25 cm. Regarding neonatal gender, 21 neonates out of 40 neonates (52.5%) were males and 19 neonates (47.5%) were females. Mother’s age ranged from 19 to 35 years with a mean of 27.47±4.46 years. IGF- 1α concentration, it ranged from 13.55 ng/ml to 163.34 ng/ml with a mean of 99.64±32.43 ng/ml and there was statistically significant decrease in neonates with restricted growth when compared to non-restricted growth group (77.67±30.92 ng/ml vs 121.62±13.64 ng/ml respectively). Conclusion: There was significant correlation between IGF-1α and weight and head circumference of preterm neonates. J Nepal Paediatr Soc 2016;36(1):24-27